SISTEM INFORMASI PENJUALAN DAN PEMBELIAN OBAT (Studi Kasus : Apotek Emulinda Bandung) - Novrini Hasti; Dani Setiadi (Jurnal Teknologi dan Informasi (JATI), 2014)
Emulinda Pharmacy is a pharmacy that is growing and moving in the field of health care, especially in the case of sale of drugs both prescription and no prescription. Pharmacy plays a very important for the health of the general public. In the process of the sales transaction, Emulinda Pharmacy requires data accuracy and time efficiency when serving customers for consumer satisfaction itself.. In addition there are many issues that arise in the current system, as well as difficulty finding medical supplies and information reporting process and the purchase of medical supplies sales take a long time. So to overcome these problems, designed a information systems and database applications that can accommodate large amounts of data so that when done accessing the data through an application process that is built to make it easier for users to obtain information. The purpose of this research was to determine the Sales and Purchase Information Systems running drugs in Emulinda Pharmacy and give a description of the systems running on this Emulinda Pharmacies, then create system design, implementation, and testing of Information Systems Sales and Purchasing Drugs proposed to to answer or solve the problems faced and to facilitate the work in data management.The design of the system used by the author using data-oriented approach (data oriented) and the development of systems using model prototype, analysis and structured programming as a tool for the process, while the database application development tool using Java programming language Netbeans IDE 7.1, XAMPP MySQL as database / database server, and creating reports using iReport 5.5.0.From the results of the development of the system and the results of this research of the Sales and Purchasing Information System computerized drug that can facilitate in the sales and purchases data processing can be faster also reduces errors in data recording process, and reduce the delay in submission of the report.